МУАММОЛИ ЁНДАШУВ АСОСИДА ТАЛАБАЛАРДА ТАНҚИДИЙ ФИКРЛАШ ҚОБИЛИЯТИНИ РИВОЖЛАНТИРИШ - Кудайбергенова, Т.К.; Ибодуллаева, И.Н.; Калжанов, П. (SCIENCE and SOCIETY, 2021)
This article discusses the development of students' critical thinking skills and its consequences on the basis of a problem-based approach on the example of the subject "Civil Society" in the Higher Educational Establishments of the Republic of Uzbekistan.
Keywords: critical thinking; problem based teaching; theoretical analysis; questionnaire; conversation; interview; the method of testing and mistakes; methods of synectics; random associations